A lower admission level of interleukin-6 is associated with first-pass effect in ischemic stroke patients. (21st April 2021) - Mechtouff, Laura; Bochaton, Thomas; Paccalet, Alexandre; Crola Da Silva, Claire; Buisson, Marielle; Amaz, Camille; Derex, Laurent; Ong, Elodie; Berthezene, Yves; Dufay, Nathalie; Ovize, Michel; Mewton, Nathan; et al.
Abstract : Background: First-pass effect (FPE) defined as a complete or near-complete reperfusion achieved after a single thrombectomy pass is predictive of favorable outcome in acute ischemic stroke (AIS) patients. We aimed to assess whether admission levels of inflammatory markers are associated with FPE. Methods: HIBISCUS-STROKE (CoHort of Patients to Identify Biological and Imaging markerS of CardiovascUlar Outcomes in Stroke) includes AIS patients with large vessel occlusion treated with mechanical thrombectomy following brain MRI. C-reactive protein, interleukin (IL)-6, IL-8, IL-10, monocyte chemoattractant protein-1, soluble tumor necrosis factor receptor I, soluble form suppression of tumorigenicity 2, matrix metalloproteinase-9 (MMP-9), soluble P-selectin, and vascular cellular adhesion molecule-1 were measured in admission sera using an ELISA assay. FPE was defined as a complete or near-complete reperfusion (thrombolysis in cerebral infarction scale (TICI) 2c or 3) after the first pass. A multivariate logistic regression analysis was performed to assess independent factors associated with FPE. Results: A total of 151 patients were included. Among them, 43 (28.5%) patients had FPE. FPE was associated with low admission levels of IL-6, MMP-9, and platelet count, an older age, lack of hypertension, lack of tandem occlusion, a shorter thrombus length, and a reduced procedural time. Following multivariate analysis, a low admission level of IL-6 was associated with FPE (OR 0.66, 95% CI 0.46 to 0.94). Optimal cut-off of IL-6 level for distinguishing FPE from non-FPE was 3.0 pg/mL (sensitivity 92.3%, specificity 42.3%). Conclusion: A lower admission level of IL-6 is associated with FPE.